2018
DOI: 10.4314/jfas.v9i6s.84
|View full text |Cite
|
Sign up to set email alerts
|

Injury profile of non-contact sports for Perak SUKMA athletes

Abstract: The purpose of this study is to identify the injury profile of non-contact sports among Perak SUKMA athletes. The data from this injury is examined based on the five research questions which are nature of injury, body part, severity of injury (mild, moderate, severe), types of injury (acute or chronic), and factors of injury. The descriptive statistics was utilized to analyze the research variables. The results showed that subsequent injury (57.8%) more than new injury (42.2%) while the incidence of injuries h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The study finding revealed that most common injury location among Perak athletes in contact-sports was lower extremities (66.5%) followed by upper extremities (33.5%). This is supported by Lee et al, (2017) stated that lower extremities (51.1%) seems to be the most common injury location in non-contact sports. Study finding indicated that high incidence of ankle and knee injuries in contact-sports among Perak athletes.…”
Section: Figure 3: Percentage Distributions On Common Factors Of Injuries Among Perak Athletes In Contact-sports Discussionmentioning
confidence: 57%
“…The study finding revealed that most common injury location among Perak athletes in contact-sports was lower extremities (66.5%) followed by upper extremities (33.5%). This is supported by Lee et al, (2017) stated that lower extremities (51.1%) seems to be the most common injury location in non-contact sports. Study finding indicated that high incidence of ankle and knee injuries in contact-sports among Perak athletes.…”
Section: Figure 3: Percentage Distributions On Common Factors Of Injuries Among Perak Athletes In Contact-sports Discussionmentioning
confidence: 57%
“…However, research indicates that the opposite is in fact the case. Research conducted by (Lee et al, 2017) and (Lee & Lee, 2018) with the Perak SUKMA athletes revealed that of the 405 non-contact-sport athletes observed, 135 reported injuries, whereas of 533 contact-sport athletes only 105 claimed some form of injury. These results suggest that a higher proportion of injured athletes exist among non-contact sports, contrary to popular belief.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction 1 Lower extremity injuries often occur on sports and physical activities that required individuals for rapid dynamic movements such as running, jumping, turning and changing direction. Lower extremity is considered as the most common injury location accounted to 51.1%, and 66.5% respectively for Malaysian athletes who participated in contact and non-contact sports [1,2]. According to Lee & Lee, poor postural stability is a contributing factor for lower extremity injures [3].…”
mentioning
confidence: 99%